La revolución hispana a debate: lecturas recientes sobre la influencia del proceso gaditano en México - Galante, Mirian (Revista Complutense de Historia de América, 2008)
In this paper a review of the recent historiography about the repercussion of the gaditan liberalism in Mexico is proposed. Productions about this topic recover the debate on the modern and revolutionary sign of the hispanic liberalism and the major or minor success on the aplication of its principles for the politic organization of the country. Generally those who present a negative view start from previous idealistic models or offer valuations from which evaluate the gaditan process in Mexico; meanwhile those who defend the positive view place this revolution on the cultural hispanic tradition and judge its success on the historical context.